Reversible Severe Pulmonary Hypertension after Adenotonsillectomy: A Case Report of a Child Treated at Bugando Medical Centre, Northwestern Tanzania. (22nd August 2016) - Kabyemera, Rogatus; Chami, Neema; Kayange, Neema; Bakalemwa, Respicius; Zuechner, Antke; Mhada, Tumaini; Buname, Gustave; Hokororo, Adolfine; Kataraihya, Johannes
Abstract : Upper airway obstruction (UAO) due to adenotonsillar hypertrophy represents one of the rare causes of pulmonary hypertension in children. We report a case of adenotonsillar hypertrophy, managed at pediatric and otorhinolaryngology departments in Bugando Medical Centre (BMC), northwestern Tanzania, with complete remission of symptoms of pulmonary hypertension following adenotonsillectomy. A 17-month-old boy presented with difficulty breathing, dry cough, and noisy breathing since 1 year. He had facial and lower limb oedema with a pan systolic murmur at the tricuspid area, fine crepitations, and tender hepatomegaly. A grade II tonsillar hypertrophy and hypertrophied adenoids were seen on nasal and throat evaluation. A 2D-echocardiography showed grossly distended right atrium and ventricle, dilated pulmonary artery, and grade III tricuspid regurgitation. His final diagnosis was severe pulmonary hypertension with right-sided heart failure due to adenotonsillar hypertrophy. He had complete remission of cardiopulmonary symptoms after adenotonsillectomy and had normal control echocardiography six and twelve months after surgery. Children with symptoms of upper airway obstruction and cardiopulmonary involvement could benefit from routine screening for pulmonary hypertension. Adenotonsillectomy should be considered for possible complete remission of both UAO and cardiopulmonary symptoms.